Keyakinan Atas Pertolongan Allah: Analisis Semiotika Roland Barthes Terhadap Kata Dallan Dalam QS. Ad-Duha [93]:7 - Ahmad Afifi (STAI KH. MUHAMMAD ALI SHODIQ TULUNGAGUNG, 2025)
The Qur’an possesses a distinctive linguistic structure, making it not always easy to understand. Some expressions may be misunderstood, such as the word ḍallan in QS. Aḍ-Ḍuḥā [93]:7, which literally means one who is astray and appears to conflict with the concept of prophetic infallibility. This study identifies two research questions: first, how the meaning of ḍallan can be analyzed through Roland Barthes’ semiotics so that it aligns with the concept of the Prophet’s infallibility; and second, how the underlying ideology and message can be uncovered. This research employs a qualitative library-study method, drawing on works related to Roland Barthes’ semiotics, literature on the literal meaning of ḍallan, as well as tafsīr bil ma’sūr and bir-ra’y relevant to QS. Aḍ-Ḍuḥā [93]:7. The study concludes that Barthes’ semiotics allows the meaning of ḍallan to remain consistent with the concept of prophetic infallibility. At the connotative level, ḍallan refers to the Prophet’s state of uncertainty prior to receiving the truth, functioning as a preparatory phase for revelation rather than an indication of misguidance. This interpretation reveals the ideology that humans cannot navigate life without divine guidance and authority, and conveys the message of the importance of trusting in God’s help and guidance when facing difficulties. Keywords: Ḍallan, Roland Barthes’s Semiotics, Belief in Divine Assistance